Acculturating autocrats: Tracing compliance with the international counter-terror regime through an analysis of Chad and Libya, 2000-2016 - Shinhearl, Brandon (AUC Knowledge Fountain, 2019)
Compliance with international regimes is a common occurrence in global politics. States often converge towards specific and shared interests and thereby construct principles, norms, rules, and procedures that state behavior within these issue-areas. International regimes encourage states to make changes to their domestic and foreign policies in order to orderly harmonize cooperation, reinforced by benefit. After 9/11 and in the context of global concerns of the international security environment, the international counter-terror regime (ICTR) has induced states to converge towards action regarding terrorism. This regime rests upon specific sets of principles, norms, rules, and procedures aimed at organizing, governing, and rewarding state behavior within this issue-area. As such, this thesis examines why and how authoritarian states comply with the international counter-terror regime in order to receive various economic, political, and military benefits that reinforce their maintenance of political power. Through a lens of constructivism and the method of process-tracing, the work offers in-depth analysis of two case studies, namely Chad and Libya ( 2000-2016). The purpose of the study is to understand compliance in the international system beyond power politics and rational choice by demonstrating how agents use identity, beliefs, ideas, and norms to reproduce international regime structure and influence the behavior of other participating states. With these cases as evidence, the thesis illustrates how authoritarians use global politics and international relations to reproduce their political power at home.